The specifics of mass culture in the era of digitalization - L. V. Filindash (Вестник университета)
The article is devoted to new features of mass culture at the digital stage of modern civilization. The emphasis is on the conceptual aspects of the phenomenon under study, its universalism in the context of informational, socio-cultural innovations. The author asserts the idea of the entry of samples and the use of the value fund of the elite level into popular culture. Immersive technologies provide the process of including a wide range of consumers in an alternative, virtual art environment. The specifics of this integration process are considered on the example of museum and gallery activities. Such methods for creating multimedia shows attractive to the mass consciousness as animation, fragmentation, compilation are revealed. The author concludes about the prospect of further coupling of elite and mass cultures. On this basis, the author highlights changes in the value potential, content and semiotic field of cultural products of the digital age, as well as socially significant consequences of bilateral adaptation processes, both counter and separate, both joint and opposite. It is necessary to note the multifactorial, multidirectional nature of cultural metamorphoses associated with the priority of virtual reality, the value of a copy, digital artifact on a par with the original.